As equipes de saúde da família e o processo de trabalho no cuidado aos pacientes com hipertensão arterial sistêmica e Diabetes Mellitus nos distritos de saúde Leste e Sul de Manaus-AM, no período da pandemia de COVID-19 Manaus - Duarte, Vanderlane de Souza (2023)
The objective of this study was to describe the work process of the family health teams (EqSF) in the care of patients with systemic arterial hypertension (HAS) and diabetes mellitus during the COVID-19 pandemic, from the health districts (DISA) East and South in the municipality of Manaus-AM. This is a descriptive study, with a quantitative approach, in which nursing professionals from the EqSF of DISA East and South in Manaus-AM, who work in caring for patients with HAS and DM, took part. Data were collected in person directly with nursing professionals, using questions from the National Program for Access and Quality Improvement in Primary Care (PMAQ-AB) instrument, in the External Assessment component, of cycle 1, addressing module I referring to the evaluation of the conditions of infrastructure, materials, inputs, and medicines of the Basic Health Units (UBS) and module II, related to information on the team's work process and on the organization of care for the user. The results were tabulated in a Microsoft Excel® database, in which the variables of interest were selected and descriptive analysis was performed using the SPSS® version 20.0 IBM® program. From a total of 96 EqSF from East and South DISA, a sample of 77 teams was instituted, according to the sample calculations. Of this sample, 59.74% (n=46) of the teams were composed of female nursing professionals, 57.14% (n=44) of these professionals were aged between 40 and 49 years and 53.25% (n =41) had additional training in areas not related to their work in Primary Health Care (APS). The layout of the EqSF showed different arrangements, 50.65% (n=39) were teams linked to other health units and 46.75% (n=36) were inserted in large Basic Health Units (UBS). There was a lack of a dentist in 9.52% (n=2) of the teams, a physician in 7.79% (n=6), and a Community Health Agent (ACS) in 1.30% (n= 1) and 11.69% (n=9) of these teams had only one ACS. Among the essential exams necessary for users with HAS and DM, the examination of the fundus of the eye was the one with the lowest percentage of performance, 15.58% (n=12). Welcoming was implemented in 98.70% (n=76) of the UBS surveyed, but 100% (n=77) of them did not use protocols with therapeutic guidelines for spontaneous demand/urgency and, regarding home visits, results were verified above 85% for all items inherent to this item. This study allowed an analysis of aspects that characterize the work process of the EqSF, in the care of patients with HAS and DM, enabling the identification of critical nodes such as the lack of adequate infrastructure for the health care of users, including the failure to perform the eye fundus examination and the lack of some professionals who make up the team, as is the case of the ACS